Association Between Periodontal Pathogens and Severity of Periodontal Diseases Among Adolescents in Kunming City: China - Xu, Jie; Pahumunto, Nuntiya; Naorungroj, Supawadee; Teanpaisan, Rawee (Journal of Health Science and Medical Research, 2024)
Objective: To investigate the association between periodontal pathogens and periodontal status among adolescents in Kunming City. Material and Methods: A total of 560 adolescents from five high schools within five urban districts in Kunming participated in this study. Clinical periodontal examination was assessed, and the levels of Porphyromonas gingivalis (P. gingivalis), Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans), Prevotella intermedia (P. intermedia), and Fusobacterium nucleatum (F. nucleatum) in saliva samples were examined using a real-time polymerase chain reaction (PCR). The relationship between periodontal pathogens and the severity of periodontal disease was investigated using multivariate logistic regression analysis. Results: The presence of P. gingivalis, A. actinomycetemcomitans, and P. intermedia was positively correlated with the extent of probing depth, clinical attachment level (CAL), and bleeding on probing. P. gingivalis and A. actinomycetemcomitans were detected at approximately 55-58% among adolescents with healthy periodontal status. P. gingivalis and A. actinomycetemcomitans were detected in all adolescents diagnosed with periodontitis (stage I or II), which was an increased number compared to healthy adolescents. It was found that P. gingivalis (odd ratio (OR)=7.03, 95% confidence interval (CI) 3.77-13.11) and A. actinomycetemcomitans (OR=5.37, 95% CI 2.73-10.57) were strongly associated with stage II periodontitis. F. nucleatum had no significant relationship with the occurrence of gingivitis and periodontitis. Conclusion: P. gingivalis, A. actinomycetemcomitans, and P. intermedia are important microbiological risk factors for periodontal diseases in adolescents.